PENGEMBANGAN MODEL REVITALISASI OLAHRAGA TRADISIONAL MENJADI SPORT FOR ALL PADA MASYARAKAT SUKU DAYAK DARI PERSPEKTIF FENOMENOLOGI - Abd. Rahman Azahari (Konstruktivisme : Jurnal Pendidikan dan Pembelajaran, 2016)
This study aims to describe steps to revitalize traditional sports to become sports for all for Dayak Society in Central Kalimantan. The study used qualitative approach implementing phenomenology aspiring perception of athletes of the traditional sports. The study was conducted in July to December 2015 invomving informants from social heads, traditional heads, sportmen, sport teachers, students majoring in sports and public. Data were collected using participatory observation and an indepth interview. Data were analyzed using qualitative procedures: collecting, reduction, classification and conclusion drawing. The study revealed that the best model to internalize and sustain traditional sports to become sport for all for Dayak Traditional Sports in Central Kalimantan includes: conducting festivals, tournaments, and inducing traditional sports in the local curriculum across school levels.